Pemutakhiran Data Pemilih Berkualitas di Kelurahan Malasilen Kota Sorong - Mustikawati, Diana; Banggu, Masni; Wahid, Bustamin; Ula, Siti Nurul Nikmatul; Purwanti, Nanik (Universitas Muhammadiyah Sorong, 2024)
General elections are a constitutional mandate and a manifestation of popular sovereignty. This democratic process aims to create circulation of government elite power, limiting the desire of political elites to perpetuate power. A form of protecting citizens' voting rights is the inclusion of voters' names in the Permanent Voter List through a continuous voter data updating process. The aim of this research is to determine the Process and Form of Coordination in Continuous Voter Data Updating in realizing a Quality Voter List in Malasilen Subdistrict, North Sorong District. This research uses a qualitative-descriptive approach. The implementation of continuous updating of voter data in Malasilen Village, North Sorong District, has been carried out in accordance with the established updating stages. There are findings that are casuistic in nature, namely a) TMS voter data was found, b) new voters were found, c) voters were found whose population data had changed. The form of coordination in this process is horizontal coordination, where this form of coordination is established between Pantarlih, RT and RW, PPS and Pantarlih. Vertical Coordination, intertwined bottom-up and top-down. The top-down model is instructional or directive in nature, and the bottom-up model is reporting on the progress of instructions.